Knowledge, attitudes, and practices of vocational college teachers towards occupational burnout - Li, Hongbing; Chen, Jiangyun; Wei, Qing; Chen, Haohao (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to investigate the knowledge, attitudes, and practices (KAP) of vocational college teachers regarding occupational burnout.MethodsA cross-sectional study was conducted among teachers from 15 vocational colleges between 20 April 2024 and 20 June 2024. Basic demographic information and KAP scores were collected through a self-developed questionnaire. The Maslach Burnout Inventory-Educators Survey (MBI-ES) was used to assess levels of occupational burnout.ResultsA total of 462 valid questionnaires were analysed, of which 264 (57.14%) respondents were female. The mean knowledge, attitude, and practice scores were 10.04 ± 4.61 (possible range: 0–18), 28.24 ± 3.77 (possible range: 7–35), and 16.68 ± 4.01 (possible range: 6–30), respectively. Multivariate linear regression analysis indicated that knowledge score (β = −0.137, 95% CI: −0.251 to −0.024, p = 0.018), attitude score (β = −0.284, 95% CI: −0.424 to −0.145, p < 0.001), practice score (β = 0.320, 95% CI: 0.193 to 0.446, p < 0.001), and sleep disorders (β = −1.915, 95% CI: −3.345 to −0.486, p = 0.009) were independently associated with MBI-ES scores. Structural equation modeling revealed that knowledge directly influenced attitude (β = 0.410, p < 0.001) and practice (β = 0.312, p = 0.001). Knowledge (β = −0.92, p = 0.024), attitude (β = −2.850, p < 0.001), and practice (β = 1.525, p < 0.001) directly affected burnout.ConclusionAlthough vocational college teachers demonstrate positive attitudes towards addressing occupational burnout, they exhibit insufficient knowledge and passive practices, leading to an increased risk of burnout. Targeted educational interventions are necessary to enhance vocational college teachers’ knowledge and skills in managing occupational burnout.